SISTEM INFORMASI PENGOLAHAN DATA LAPORAN STATISTIK PERTANIAN TANAMAN PANGAN STUDI KASUS (KOTO GADIH) PAYAKUMBUH - Fajri, Ahmad Fikri (Jurnal Sains dan Informatika, 2017)
In the framework of improving agricultural performance, almost all agriculture seeks to make changes to the work system because the system is applied almost unfit for use for agricultural operations especially in the processing of data complex and routine. The main reasons for the use of information technology in data processing of statistical reports pertanin is efficiency, time and cost savings. Besides the increased effectiveness, achieving the output of agricultural statistical data reports correctly is a necessity of every agriculture. Due to the important role of information technology, information technology becomes something that is required to support activities. In this study the authors use Field Researce method is to conduct direct research into the field, from the results of collected data, then the author uses Laboratory Researce method is to process the results of research data in computer labor and then the author also uses Library Research method of conducting library research. From the results of this study can be designed a system of agricultural statistical reports, which in the design is carried out the development of information generated from the old system and there is a way of working from the system itself by using the computer as a tool. It is expected that this information system can help and facilitate employees in processing the data